AAV-S: A versatile capsid variant for transduction of mouse and primate inner ear - Ivanchenko, Maryna V. (Mol Ther Methods Clin Dev, 2021)
Gene therapy strategies using adeno-associated virus (AAV) vectors to treat hereditary deafnesses have shown remarkable efficacy in some mouse models of hearing loss. Even so, there are few AAV capsids that transduce both inner and outer hair cells—the cells that express most deafness genes—and fewer still shown to transduce hair cells efficiently in primates. AAV capsids with robust transduction of inner and outer hair cells in primate cochlea will be needed for most clinical trials. Here, we test a capsid that we previously isolated from a random capsid library, AAV-S, for transduction in mouse and non-human primate inner ear. In both mice and cynomolgus macaques, AAV-S mediates highly efficient reporter gene expression in a variety of cochlear cells, including inner and outer hair cells, fibrocytes, and supporting cells. In a mouse model of Usher syndrome type 3A, AAV-S encoding CLRN1 robustly and durably rescues hearing. Overall, our data indicate that AAV-S is a promising candidate for therapeutic gene delivery to the human inner ear.